Effects of dexmedetomidine and MK-467 on plasma glucose, insulin and glucagon in a glibenclamide-induced canine hypoglycaemia model. (December 2018) - Kallio-Kujala, I.J.; Bennett, R.C.; Raekallio, M.R.; Yatkin, E.; Meierjohann, A.; Savontaus, E.; Scheinin, M.; Spillmann, T.; Vainio, O.M.
Highlights: Effects of the sedative drug combination dexmedetomidine and MK-467 were tested in a canine hypoglycaemia model. Concentrations of glucose, insulin, glucagon, lactate, dexmedetomidine and MK-467 in plasma were measured. Dexmedetomidine counteracted glibenclamide-evoked hypoglycaemia; this was opposed by concomitantly administered MK-467. Glibenclamide-induced hypoglycaemia was not exacerbated by co-administered dexmedetomidine and MK-467. Abstract: The commonly used sedative α2 -adrenoceptor agonist dexmedetomidine has adverse cardiovascular effects in dogs that can be prevented by concomitant administration of the peripherally acting α2 -adrenoceptor antagonist MK-467. An ancillary effect of dexmedetomidine is to decrease insulin release from the pancreas, whereas MK-467 stimulates insulin release. This study assessed the effects of co-administered dexmedetomidine and MK-467 in a canine glibenclamide-induced hypoglycaemia model. In a randomised, cross-over experiment, eight beagle dogs received five intravenous treatments, comprising two administrations of saline, with dexmedetomidine or dexmedetomidine and MK-467, and three administrations of glibenclamide, with saline, dexmedetomidine or dexmedetomidine and MK-467. Plasma concentrations of glucose, lactate, insulin, glucagon and the test drugs were monitored. Administration of glibenclamide significantly increased insulin secretion and decreased blood glucose concentrations. Dexmedetomidine counteracted glibenclamide-evoked hypoglycaemia. This was opposed by the α2 -adrenoceptor antagonist MK-467, but the glibenclamide-evoked hypoglycaemia was not potentiated by co-administration of dexmedetomidine and MK-467. None of the dogs developed uncontrolled hypoglycaemia. Thus, the combination of dexmedetomidine and MK-467 appeared to be safe in this canine hypoglycaemia model. Nevertheless, when MK-467 is used to alleviate the undesired cardiovascular effects of α2 -adrenoceptor agonists in dogs, it should be used with caution in animals at risk for hypoglycaemia because of its insulin-releasing and hypoglycaemic effects.